Electron Transfer Processes in Biologically Relevant Molecules. An Experimental Study of Neutral Alkali Atom-Molecule Collisions - Kumar, Sarvesh (2022)
The work developed within the context of this thesis includes negative ion formation in charge transfer processes from collisions of neutral potassium atoms with key selected neutral mole-cules. The crossed molecular beam set up used to obtain the anion yields as a function of the collision energy as well as relevant information about the lowest-lying anionic states that are accessed in the temporary negative ion formation, is fully equipped with a time−of−flight mass spectrometer and an energy loss analyser. The spectrometric technique includes a linear and a reflectron type time-of-flight mass spectrometers to provide information about the neg-ative ions formed in such collisions. We have made use of a home−built Wiley McLaren type Linear Time-of-flight mass spectrometer (L−TOF−MS), to extract relevant information about the kinetic energy release distribution of selected fragment anions, as a function of the collision energy, while the reflectron time−of−flight mass-spectrometer (r−TOF−MS) was used due to its higher mass resolution serving as a proper tool to resolve close lying fragment anions dif-fering by just 1 amu in the fragmentation of nimorazole. In order to obtain relevant infor-mation about the most accessed negative ion states in the collision process, a post−collision potassium cation (K+) energy loss spectra in the forward scattering direction (θ ≈ 0°) with the beam's optical path have been recorded in a hemispherical energy loss analyser. The combi-nation of TOF−MS and these two techniques helped us to gain deep insight into electron trans-fer processes of molecules under investigation. The set of chlorinated molecules investigated include a group (C6H5Cl,C6D5Cl, C6H11Cl,and C6Cl6) that has been properly chosen to explore the role of direct dissociation through electron transfer into a σCl∗ antibonding orbital and more importantly to determine the role of intramolecular electron transfer through π∗σCl∗⁄ coupling yielding anion formation. From the comprehensive investigation of these molecules in a wide energy range of collision energies, 10 − 103 eV in lab frame, we have obtained for the first time the relative cross−sec-tion for Cl− formation. The other group of molecules include biological relevant targets as the radiosensitizer nimorazole (NIMO) and water. Regarding the former, although the major signal is assigned to the non-dissociated parent anion (80% of the total anion yield), NO2− accounts for just 10−15% of the total anion yield a detailed trace fragmentation pattern indicates decomposition of NIMO's 4−nitroimidazole and morpholine rings. As far as the latter is concerned, H2O and its deuterated counterpart D2O were investigated and are presented in the third part of this thesis. The fragmentation pattern from H2O includes H−, O−, and OH− whereas from D2O in-cludes D−, O−, and OD−. From the different TOF mass spectra the fragment anions' thresholds of formation have been obtained. K+ energy loss spectra from NIMO, H2O and D2O were also recorded, revealing the experimental vertical electron affinities of the most accessed negative ion states.